Long-Term Effect of Sublingual and Subcutaneous Immunotherapy in Dust Mite-Allergic Children With Asthma/Rhinitis: A 3-Year Prospective Randomized Controlled Trial - (:unkn) unknown (ESMON PUBLICIDAD S A, DEPT ALLERGY & CLIN IMMUNOL, CLIN UNIV NAVARRA, 2015)
Background and Objective: Specific allergen immunotherapy is the only treatment modality that might change the natural course of allergic diseases in childhood. We sought to prospectively compare the long-term clinical and immunological effects of sublingual (SLIT) and subcutaneous (SCIT) immunotherapy compared with pharmacotherapy alone. Methods: In this single-center, prospective randomized controlled trial, 48 children with mild persistent asthma with/without rhinitis, monosensitized to house dust mites (HDMs) were followed for 3 years. At baseline and years 1 and 3 of follow-up, patients were evaluated and compared for total rhinitis (TRSS) and asthma (TASS) symptom scores, total symptom scores (TSS), total medication scores (TMS), safety profiles, skin-nasal-bronchial reactivity, and immunological parameters. Results:A significant reduction was observed in TASS for both HDM-SCIT and HDM-SLIT at year 3 of treatment compared with baseline and controls (P<.05 for both), with significant improvement in rhinitis symptoms for both groups compared with controls (P=.01 for both). TSS decreased significantly in both HDM-SCIT and HDM-SLIT at year 3 compared with baseline (P=.007 and P=.04, respectively) and controls (P<.01 for both). A significant reduction in TMS was observed in HDM-SCIT and HDM-SLIT compared with baseline and controls (P=.01 in all cases), with a reduction in skin reactivity to HDM (P<.05). Finally, a significant increase in allergen specific IgG4 was observed in the SCIT group at year 3 compared with baseline, the SLIT group, and controls (P<.001 in all cases). Conclusions: HDM-sensitized asthmatic children treated for at least 3 years with either SCIT or SLIT showed sustained clinical improvement.
Keywords: Asthma; Children; House dust mites; Immunotherapy; Subcutaneous immunotherapy; Sublingual immunotherapy; RESPIRATORY ALLERGY; DOUBLE-BLIND; ASTHMA; EFFICACY; RHINITIS; PARAMETERS; MECHANISMS; CHILDHOOD